PENGARUH INFLASI, SUKU BUNGA, DAN KURS TERHADAP RETURN SAHAM DI BURSA EFEK INDONESIA (Studi pada perusahaan manufaktur periode 2018-2022) - Ningsih, Fitria; Nofiana, Lina (Journal of Research and Publication Innovation, 2024)
This research was conducted to determine the influence of inflation, interest rates and exchange rates on stock returns on the Indonesia Stock Exchange in a study of manufacturing companies for the 2018-2022 period. This research uses quantitative research. The data collection methods used in this research are time series and cross section data, namely panel data. The number of samples in this research was 10 manufacturing companies listed on the Indonesia Stock Exchange for the 2018- 2022 period. The data analysis methods in this research are classical assumption testing, multiple regression analysis and hypothesis testing which is processed using Eviews 12. Hypothesis testing via the t test produces results that inflation, interest rates and exchange rates do not have a significant effect on manufacturing company stock returns. The results of the F test in this research are the calculated F of 0.281571 or above the criterion value of 0.05. The results of the regression coefficient, Inflation, Interest Rates and Exchange Rates have an influence of 0.018806 or 1.88% on the stock returns of manufacturing companies on the Indonesia Stock Exchange for the 2018-2022 period.